2020
DOI: 10.21037/qims-20-638
|View full text |Cite
|
Sign up to set email alerts
|

Virtual multidisciplinary team meetings in the age of COVID-19: an effective and pragmatic alternative

Abstract: The ongoing severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic and the associated coronavirus disease 2019 have had a profound global and individual burden, with 1,610,909 confirmed cases and 99,690 confirmed deaths across 213 countries, areas, and territories at the time of writing (1).The highly transmissible nature of the novel coronavirus, its potential for asymptomatic transmission, and the lack of a curative treatment, has necessitated the enforcement of stringent social distancing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
58
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 5 publications
9
58
0
1
Order By: Relevance
“…This factor helped in building stronger relationships, better team working and encouraged more robust conversations. This result was similar to the findings in a survey among participants of an MDT where virtual platforms had been implemented, in which 42% participants preferred ‘face-to-face’ MDTs for the same reasons [ 25 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This factor helped in building stronger relationships, better team working and encouraged more robust conversations. This result was similar to the findings in a survey among participants of an MDT where virtual platforms had been implemented, in which 42% participants preferred ‘face-to-face’ MDTs for the same reasons [ 25 ].…”
Section: Discussionsupporting
confidence: 87%
“…Two other key factors, ‘change in treatment plan’ and ‘decision making to achieve diagnosis’ also was found to be unaffected compared to face-to-face MDTs, as reported by the majority of the participants. A survey among participants who had been in virtual meetings involving head and neck cancers showed that 91.7% of them felt good access to patient data and adequate discussion over virtual platforms [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This factor helped in building stronger relationships, better team working and encouraged more robust conversations. This result was similar to the ndings in a survey among participants of an MDT where virtual platforms had been implemented, in which 42% participants preferred 'face-to-face' MDTs for the same reasons 23 .…”
Section: Discussionsupporting
confidence: 86%
“…Two other key factors, 'change in treatment plan' and 'decision making to achieve diagnosis' also was found to be unaffected compared to face-to-face MDTs, as reported by the majority of the participants. A survey among participants who had been in virtual meetings involving head and neck cancers showed that 91.7% of them felt good access to patient data and adequate discussion over virtual platforms 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Many cancer centres have gone onto virtual cancer multidisciplinary team (MDT) meetings using various platforms including Microsoft Teams to ensure socially distant meetings. 39 This pragmatic approach has been welcomed by all health disciplines to ensure that multidisciplinary cancer team discussions continue to occur in a timely and safe approach during the COVID-19 pandemic 40 This platform has allowed specialized clinicians and teams to access meetings remotely, having a presence in meetings they may not have had access to prior to the pandemic, providing high quality advice to teams and care to patients. It is important for healthcare organisations to ensure that such platforms are safe and secure in keeping with data protection legislation.…”
Section: Virtual Multidisciplinary Team Meetingsmentioning
confidence: 99%